Influence of Color Education and Training on Shade Matching Skills. Issue 5 (7th April 2016) - Ristic, Ivan; Stankovic, Sasa; Paravina, Rade D
Abstract: Objectives: To evaluate the influence of education and training on quality of tooth color matching. Material and Methods: Dental students (N = 174), matched the color of eight shade tabs in a viewing booth, using VITA Linearguide 3D‐Master shade guide. The experimental group had color education and training between the before and after session. The control group did not have any additional information in between two sessions. Color differences between the task tabs and selected tabs were calculated using CIE formulas. The score for the best match (smallest color difference) was 10 points, the 2nd best match 9 points, down to 1 point for the 10th best match. Means and standard deviations were calculated. Differences were analyzed using the Student t‐test. Results: Shade matching scores in the experimental group were significantly better after education and training (p < 0.001), with a mean score before and after shade matching sessions of 7.06 (1.19) and 8.43 (0.92), respectively. The percentage of students in the experimental group that selected one of three best matches increased 24.3%. The control group exhibited no significant improvement in the after session. Conclusions: Within the limitations of the study, education and training improved students' shade matching skills. Clinical Significance: While the vast majority of dental restorations and practically all restorations in the esthetic zone are tooth colored, the profession as a whole is far from perfect when it comes to accurate shade matching. Education and training can improve shade matching ability: enhanced esthetics of dental restorations, increased patient satisfaction, and a reduced number of color corrections are some of the notable benefits and rewards. (J Esthet Restor Dent 00:000–000, 2016) J Esthet Restor Dent 28:287–294, 2016)